Development of a mitochondrial DNA real‐time polymerase chain reaction assay for quality control of pathogen reduction with riboflavin and ultraviolet light. Issue 4 (27th June 2014) - Bakkour, S.; Chafets, D. M.; Wen, L.; van der Meer, P. F.; Mundt, J. M.; Marschner, S.; Goodrich, R. P.; Busch, M. P.; Lee, T.‐H.
<x xml:space="preserve">Abstract</x> Background and Objectives Transfusion is associated with a risk of infection and alloimmunization. Pathogen reduction using riboflavin and UV light (Mirasol treatment) inactivates pathogens and leucocytes. With increasing adoption of the technology in clinical use, regulatory agencies have recommended the introduction of quality control measures to monitor pathogen reduction efficacy. We sought to develop a real‐time PCR‐based assay to document the impact of pathogen reduction on the mitochondrial genome in blood components. Materials and Methods DNA was extracted from platelet and plasma components before and after treatment with riboflavin and UV light. Inhibition of PCR amplification of mitochondrial DNA (mtDNA) in short‐ and long‐amplicon target regions, ranging from under 200 base pairs (bp) to over 1800 bp, was measured in treated relative to untreated components. Results Pathogen reduction of platelets using riboflavin and UV light resulted in inhibition of PCR amplification of long‐amplicon mtDNA targets, demonstrating approximately 1 log reduction of amplification relative to untreated products. Amplification of short‐amplicon mtDNA targets was not affected by treatment. Evaluation of 110 blinded platelet samples from the PREPAReS clinical trial resulted in prediction of treatment status with 100% accuracy. Pathogen reduction of plasma components resulted in similar levels of PCR inhibition, while testing of 30 blinded plasma samples resulted in prediction of treatment status with 93% accuracy. Conclusion A differential sized amplicon real‐time PCR assay of mitochondrial DNA effectively documents nucleic acid damage induced by Mirasol treatment of platelets. The use of the assay for plasma product pathogen reduction requires further investigation.